Copper Coins, Catchwords, and Contextual Cues: The Climactic Placement of the Widow’s Mites (Mark 12:41–44) - Jeremy D. Otten (Tyndale Bulletin, 2023)
The story of the widow in the temple with her two small copper coins (Mark 12:41-44) is a familiar one, but recent scholarship has yielded a surprisingly divergent array of interpretative options. In particular, in noting the catchword χήρα (vv. 40,42,43) that links this episode to Jesus’s diatribe against the scribes in the preceding pericope (vv. 38-40), recent scholarship has argued, against the traditionally positive interpretation of this narrative, that this context requires a negative or tragic interpretation. The present study argues that catchwords and other contextual clues link the widow narrative not just with the preceding pericope, but with the whole series of five disputations in the temple (vv. 13-40). With the episode functioning in this way as an epilogue to the whole section, the widow may be seen as both a model of discipleship as well as a tragic figure whose poverty illustrates the failure of the religious leadership. Because catchwords are frequently noted but rarely defined, criteria must first be proposed for their identification and verification. These are then applied to the passage in question to demonstrate the lexical and semantic links between it and the preceding passages. Seen in this context, the widow narrative emerges in both greater clarity and greater complexity, illustrating piety and true discipleship on the one hand, and the tragic failure of the temple cult and its leaders on the other.